What is out there? A typology of land restoration projects in Latin America and the Caribbean - Coppus, Ruben; Romijn, J.E.; Méndez Toribio, M.; Murcia, C.; Thomas, E.; Guariguata, Manuel R.; Herold, M.; Verchot, Louis V. (IOP Publishing, 2019)
Restoring degraded lands is high on the international agenda and the number of restoration projects in Latin America and the Caribbean (LAC) has increased considerably over the past decades. However, the variety of approaches used have not been systematically documented and analyzed. We aimed to develop a restoration typology as a function of the geographical and socio-economical setting, planning, timeframe, finances, implementation, monitoring and potential impact, which will help to discern broad patterns and identify gaps in project implementation in LAC. We categorized 97 restoration projects using Multiple Correspondence Analysis and a Hierarchical Clustering on Principal Components. Three main restoration types emerged from the clustering, with the main defining variables being: (1) project area under restoration, (2) amount of funding received, (3) source of funding and (4) monitoring efforts. The first type are large-scale projects, which receive high amounts of funding provided by international donors, and with a well-established monitoring plan; the second type are projects financed with private money, typically lacking a sound monitoring program; and the third type represents small projects with low amounts of funding, financed with public funds from national governments, often with a rudimentary monitoring plan. The typology enables a comparative analysis of the status and trends of restoration activities across Latin America. We conclude that, despite growing awareness and recognition that integrated approaches are needed to revert complex and interconnected socio-economic and environmental issues like land degradation, the socio-economic dimension remains underexposed in the majority of restoration projects, whereas monitoring is still regarded as an extra cost instead of a necessary investment.